2022
DOI: 10.1155/2022/3428229
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Evaluation of Root and Root Canal Configuration of Permanent Maxillary Dentition in the Population of the Kingdom of Saudi Arabia

Abstract: Aim. This study is aimed at combining the sample sizes of all studies on permanent maxillary teeth conducted in different regions of the Kingdom of Saudi Arabia (KSA) to obtain a large sample size that represents the population of the KSA. The outcome of these combined studies is compared with international studies in terms of the number of roots, number of canals, and canal configurations on the basis of Vertucci’s classification. Methodology. The studies were systematically reviewed using the Preferred Repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 74 publications
3
22
0
2
Order By: Relevance
“…8 An unexpected anatomy is known as an anatomical variation. 3,9 These variations are common because the internal morphology of the RC is more complex than the external morphology of the tooth. [10][11][12][13] Negligence to treat a few millimeters of tissue pulp can lead to an unsuccessful RCT.…”
mentioning
confidence: 99%
“…8 An unexpected anatomy is known as an anatomical variation. 3,9 These variations are common because the internal morphology of the RC is more complex than the external morphology of the tooth. [10][11][12][13] Negligence to treat a few millimeters of tissue pulp can lead to an unsuccessful RCT.…”
mentioning
confidence: 99%
“…A great deal of variation in maxillary rst premolar had been reported in root anatomy and root canal morphology in several studies [9][10][11]. Table 7 shows a comparison between the number of maxillary rst premolar roots in previous studies in different regions [22][23][24][25][26][27][28][29][30][31][32][33]. Ethnicity may be the greatest contributor to the variation, especially between Chinese and other populations.…”
Section: Discussionmentioning
confidence: 99%
“…The second mesiobuccal canal (MB2) in the mesiobuccal root (MBR) of PMFM is the most commonly investigated. Many studies have revealed that the prevalence of MB2 exceeds 50%, varying from 50.8% to 97.6% [7][8][9][10]. For such a high prevalence of MB2 in PMFM, clinicians should be patient and prudential to locate MB2 when treating this tooth.…”
Section: Introductionmentioning
confidence: 99%